Prognostic Effect of Guideline-Directed Therapy Is More Noticeable Early in the Course of Heart Failure - Ahn, Min-Soo; Yoo, Byung-Su; Yoon, Junghan; Lee, Seung-Hwan; Kim, Jang-Young; Ahn, Sung Gyun; Youn, Young Jin; Lee, Jun-Won; Son, Jung-Woo; Kim, Hye Sim; Kang, Dae Ryong; Lee, Sang Eun; et al. (Journal of Korean medical science, 2019)
There have been few studies to evaluate the prognostic implications of guideline-directed therapy according to the temporal course of heart failure. This study assessed the relationship between adherence to guideline-directed therapy at discharge and 60-day clinical outcomes in acute heart failure (AHF) and acute decompensated chronic heart failure (ADCHF) separately. Among 5,625 AHF patients who were recruited from a multicenter cohort registry of Korean Acute Heart Failure, 2,769 patients with reduced ejection fraction were analyzed. Guideline-directed therapies were defined as the use of angiotensin-converting enzyme inhibitor (ACEI) or angiotensin receptor II blocker (ARB), β-blocker, and mineralocorticoid receptor antagonist. In AHF, ACEI or ARB reduced re-hospitalization (hazard ratio [HR], 0.57; 95% confidence interval [CI], 0.34-0.95), mortality (HR, 0.41; 95% CI, 0.24-0.69) and composite endpoint (HR, 0.52; 95% CI, 0.36-0.77) rates. Beta-blockers reduced re-hospitalization (HR, 0.62; 95% CI, 0.41-0.95) and composite endpoint (HR, 0.65; 95% CI, 0.47-0.90) rates. In ADCHF, adherence to ACEI or ARB was associated with only mortality and β-blockers with composite endpoint. The prognostic implications of adherence to guideline-directed therapy at discharge were more pronounced in heart failure. We recommend that guideline-directed therapy be started as early as possible in the course of heart failure with reduced ejection fraction.